Hubungan Antara Media Digital dan Perkembangan Bahasa Siswa Kelas IV di SD Negeri 3 Weru Lor - Dwi Lena, Putri; Nurkholis (Jurnal Cakrawala Akademika, 2024)
This study investigates the relationship between digital media and language development among fourth-grade students at Elementary School 3 Weru Lor. The research aims to understand how digital media usage influences linguistic abilities in young learners. Utilizing a qualitative approach, data were collected through observations, interviews, and documentation. Key findings indicate a significant correlation between high digital media interaction and advanced vocabulary acquisition, yet also highlight potential risks of reduced verbal communication skills. These insights underline the need for balanced media exposure in educational strategies.